Introduction to RNAi and miRNA pathways - Petr Svoboda (Karolinum Press, 2020)
Small RNA pathways or RNA silencing is a group of pathways, which utilize small RNAs as guides for sequence-specific repression. This collection of texts has an origin in a report prepared for the EFSA in 2016 and 2017. The original text was reorganized into twelve chapters, which were reformatted and revised in order to remove copyrighted material from third parties and provide a introductory parts for stand alone chapters. Nine of the chapters focus on small RNA pathways in animals and plants. The remaining three chapters include a general introduction and reviews of important phenomena – off-targeting and extracellular small RNAs.